The anti-cancer effect of octagon and spherical silver nanoparticles on MCF-7 breast cancer cell line - Khatami, Mehrdad; Kharazi, Sam; Farahani, Zeinab Kishani; Azizi, Hakim; Nobre, Marcos Augusto Lima [UNESP] (My University, 2017)
Background: The modern science of nanotechnology is an interdisciplinary science that has contributed to advances in cancer treatment. This study was performed to evaluate the therapeutic effects of biosynthesized silver nanoparticles on breast cancer cell of line MCF-7 in vitro. Methods: This analytical study was performed in Kerman and Bam University of Medical Sciences, Bam City, Kerman Province, Iran from March 2015 to March 2016. Silver nanoparticles suspension was synthesized using palm kernel extract. The resulting silver nanoparticles were studied and characterized. The ultraviolet-visible spectroscopy and transmission electron microscopy used for screening of physicochemical properties. The average particle size of the biosynthesized silver nanoparticles was determined by transmission electron microscopy. The properties of different concentrations of synthesized silver nanoparticles (1 to 3 μg/ml) and palm kernel extract (containing the same concentration of the extract was used for the synthesis of silver nanoparticles) against MCF-7 human breast cancer cells were determined by MTT assay. MTT is used to assess cell viability as a function of redox potential. Actively respiring cells convert the water-soluble MTT to an insoluble purple formazan. Results: The ultraviolet-visible spectroscopy showed strong absorption peak at 429 nm. The X-ray diffraction (XRD) and transmission electron microscopy (TEM) images revealed the formation of silver nanoparticles with spherical and octagon shape and sizes in the range between 1-40 nm, with an average size approximately 17 nm. The anticancer effect of silver nanoparticles on cell viability was strongly depends on the concentration of silver nanoparticles and greatly decrease with increasing the concentration of silver nanoparticles. The IC50 amount of silver nanoparticle was 2 μg/ml. Conclusion: The biosynthesized silver nanoparticles showed a dose-dependent toxicity against MCF-7 human breast cancer cells.
Keywords: Breast cancer; Nanoparticles; Nanotechnology; Silver; Toxicity; Transmission electron microscopy